# |
ODE |
Mathematica |
Maple |
\[
{}y-3 x +\left (4 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+3 x y^{2}\right ) y^{\prime } = y^{3}+3 x^{2} y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{3}+3 x^{2}-2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+3 x y = 5 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 5 \,{\mathrm e}^{\cos \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}\left (3 x +3 y-4\right ) y^{\prime } = -x -y
\] |
✓ |
✓ |
|
\[
{}-x y^{2}+x = \left (x +x^{2} y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x -y-1+\left (4 y+x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x y+1\right )+x \left (1+x y+x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = y^{4} {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+y = y^{3} \left (x -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y \tan \left (x \right ) = y^{2} \tan \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = y^{3} \sec \left (x \right )^{4}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime } = x y+1
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }-\left (1+x \right ) \sqrt {y-1} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-2 x y+5 y^{2} = \left (y^{2}+2 x y+x^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \cot \left (x \right ) = y^{2} \sec \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y+\left (x^{2}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = \cos \left (x \right )-2 x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+y^{2}}{x^{2}+2 x y}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x \left (1+y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 3 x -1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}-x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x -2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -2 y+1}{2 x -4 y}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{3}+1\right ) y^{\prime }+x^{2} y = x^{2} \left (-x^{3}+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x +x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (\frac {1}{x}-\frac {2 x}{-x^{2}+1}\right ) y = \frac {1}{-x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x y = \left (x^{2}+1\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (1+y^{2}\right )-y \left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {r \tan \left (\theta \right ) r^{\prime }}{a^{2}-r^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = \left (x -1\right ) \sin \left (x \right )+\left (1+x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = 3 \,{\mathrm e}^{x}-2 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = {\mathrm e}^{x} x^{2}-x \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{2 x} x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (x \right )+\cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {4 y}{x} = x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{4}
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y^{\prime } = y \left (3 x^{2}+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}4 y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+2 y+\left (-x^{2}+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y-\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+y+\left (x^{2} y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (\frac {y}{x}\right ) x -y \cos \left (\frac {y}{x}\right )+x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (x^{2}+2\right )+\left (y^{3}+x^{3}\right ) \left (-x y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \sqrt {x^{2}+y^{2}}-x \left (\sqrt {x^{2}+y^{2}}+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1+\left (2 x +2 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+2 y-\left (4-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x +2 y+\left (3 y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-2 y = \sqrt {x^{2}+4 y^{2}}
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \left (1+y\right ) \left (1-x \right )
\] |
✓ |
✓ |
|
\[
{}y^{2}-x^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 x y+1\right )+x \left (1-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+\left (-x^{2}+1\right ) \cot \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+y^{3}+3 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}3 x +2 y+1-\left (3 x +2 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )+\left (1+{\mathrm e}^{-x}\right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -2 \left (3 y+2 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x -2 \sin \left (y\right )+3+\left (2 x -4 \sin \left (y\right )-3\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y \cos \left (x \right )+\sin \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+4+\left (3 x +4 y+5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{3} y^{3}+\frac {1}{x}+\left (3 y^{2} x^{4}-\frac {1}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 u^{2}+2 u v+\left (u^{2}+v^{2}\right ) v^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \sqrt {x^{2}+y^{2}}-y+\left (y \sqrt {x^{2}+y^{2}}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1-\left (y-x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-\frac {y}{x \left (x +y\right )}+2+\left (\frac {1}{x +y}+2 \left (1+x \right ) y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y \,{\mathrm e}^{x^{2} y}+y^{2} {\mathrm e}^{x y^{2}}+1+\left (x^{2} {\mathrm e}^{x^{2} y}+2 x y \,{\mathrm e}^{x y^{2}}-2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x -2 y\right )-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1-\sqrt {a^{2}-x^{2}}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1-\left (x -y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -x^{2}-y^{2}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y-3 x +x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|